THE MOTIVATIONS OF STUDENTS OF THE FACULTY ECONOMICS IN LEARNING ARABIC / دوافع طلاب كلية الاقتصاد في تعلم اللغة العربية - Ahmad Nurul Huda Salmas (Abjadia : International Journal of Education, 2020)
This study aims to describe intrinsic motivation and factors that influence student motivation in learning Arabic. This research is a case study developed using qualitative descriptive research methods. The sample in this study is students at the Faculty of Economics in Learning Arabic, Special Program for Arabic Language Development, Universitas Negeri of Maulana Malik Ibrahim Malang. The result shows that the intrinsic motivation of students to learn Arabic well is because Arabic is the language of the Moslems, Al-Qur’an language. Another motivation is the need to understand Islam and the hope of getting good grades and proficiency in Arabic. The results also show that the extrinsic motivation of students who liked learning Arabic was due to the excellent and pleasant environment in learning. Also, another extrinsic motivation is due to the fun activities in learning Arabic and the appreciation from lecturers or the Special Programs for Arabic Language Development. Diverse and fun teaching methods and the existence of learning activities outside the classroom and the reality of advice given by the instructor to students are also the factors that motivate students to learn Arabic